KEAMANAN MANUSIA DALAM KETERLIBATAN KANADA DI AFGHANISTAN (2002-2011) - , ROSVITA WALANDA SITORUS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis aims to answer the questions on why Canada using human security in its involvement in Afghanistan and how Canada implement the human security. To be able to measure the motives behind Canadaâs action this research using theory of international norms from Contructivist to find out why an actor using a norm in their action. First this research will see human security as a norm, new norm that affecting its norm entrepreuner. According to the theory of international norms, there are few motives behind an actorâs action at different stage of norm life cycle. Human security has been characterizing Canadaâs foreign policy in 1990s, pioneered by former minister of foreign affairs, Llyod Axworthy. As one of the norm entrepreneur Canada will have to act to certain action in purpose to keep its status/identity as norm entrepreuner of human security. This is because this status or identity is such a pride for Canada. Canadaâs relation with Afghanistan during 1968-2011 will also be explained in this research. As second question in this thesis, the remainder of this research will be describing how Canada articulate and implement human security in Afghanistan, also its programmes that held in 2002-2011. International community has seen Afghanistan as a failed state and this condition will also be explained. Afghanistanâs status as failed state has caused a new obligation to Canada as a norm entrepreuner to address this issue. Canadaâs action in Afghanistan will also be analyzed in this research. This is to see whether Canadaâs action is in line with human security or not. The finding is that Canadaâs action not merely in line with human security, a lot of flaws in implementation of Canadaâs programmes, especially in 3Ds concept (Defense, Diplomacy and Development).